Benthic-pelagic coupling and isotopic fractionation of barium in Kiel Bight, SW Baltic Sea - Scholz, Florian; Cheng, Jun; Zhang, Zhouling; Vosteen, Paul; Siebert, Christopher; Frank, Martin (Frontiers in Marine Science, 2023)
Barium (Ba) isotopes are a promising new tracer for riverine freshwater input to the ocean and marine biogeochemical cycling. However, many processes that affect Ba cycling at continental margins have not yet been investigated with respect to Ba isotope fractionation. Here, we present a comprehensive data set of Ba concentration and isotope data for water column, pore water and sediment samples from Kiel Bight, a seasonally stratified and hypoxic fjord in the southwestern Baltic Sea. The surface water Ba concentration and Ba isotope inventory of the water column can generally be explained by mixing of riverine freshwater and Atlantic seawater. However, the deep-water below the seasonal pycnocline (10 - 15 m water depth) is characterized by a pronounced positive Ba concentration anomaly (up to 915 nM) that is accompanied by a δ138Ba of ~+0.25 ‰, which is lighter than expected from the seawater-freshwater mixing line (Ba: 77 nM, δ138Ba: +0.32 ‰ at a salinity of 18). Pore water profiles indicate a Ba flux across the sediment-water interface, which contributes to the enrichment in isotopically light Ba in the deep-water. Pore waters of surface sediments and deep-waters are oversaturated with respect to barite. Therefore, barite dissolution is unlikely to account for the benthic Ba flux. Water column Ba concentrations closely correlate with those of the nutrients phosphate and silica, which are removed from surface waters by biological processes and recycled from the sediment by diffusion across the sediment-water interface. As nutrient-to-Ba ratios differ among sites and from those observed in open-marine systems, we propose that Ba is removed from surface waters by adsorption onto biogenic particles (rather than assimilation) and regenerated within surface sediments upon organic matter degradation. Pore water data for subsurface sediments in Kiel Bight indicate preferential transfer of isotopically heavy Ba into an authigenic phase during early diagenesis. Quantifying the burial flux associated with this authigenic Ba phase along continental margins could potentially help to settle the isotopic imbalance between known Ba source and sink fluxes in the ocean.